Accounting Research Within the Framework of Feminist Theory - Mazda Eko Sri Tjahjono; Lilik Purwanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Feminist theory is one of the theories that discusses how women advocate for themselves in social life. This article aims to discuss the development of feminist accounting research in Indonesia. Literature studies were chosen in this article to enrich the forms and variations of feminist accounting research. Feminist issues cannot be analyzed with a quantified gender dichotomy. The role of women in the accounting profession is quite diverse. The methods and approaches used in feminist research are commonly used in other studies. This article is expected to serve as a catalyst for the development of future feminist accounting research